Pendidikan Kedamaian sebagai Fondasi Konseling Karier: Studi Literatur tentang Etika Konselor dan Pengambilan Keputusan Siswa - Alfan Kurniawan, Nanda; Dhiffa Ralianti, Destanika; Hanafi, Husni; Widyatmoko, Wahyu; Rilo Pambudi, Parid (Jurnal Bimbingan dan Konseling Pandohop, 2026)
Peace education is not only a normative discourse but also a practical foundation for career counseling services in schools. This study aims to examine the interrelationship between the peace education paradigm, counselor ethics, and students’ career decision-making abilities. The research employed a literature review using research articles and relevant review papers as data sources. Content analysis was applied to identify the role of peace values in guiding ethical counseling practices and their contribution to students’ readiness in determining career directions. The findings indicate that peace education strengthens counselor ethics by emphasizing empathy, respect for individual dignity, and orientation toward students’ long-term well-being. The integration of these paradigms makes career counseling more humanistic, reflective, and sustainable. This study underscores the urgency of developing peace-education-based career counseling and opens opportunities for future research to integrate this paradigm with existing school counseling models.